2018
DOI: 10.1016/j.cell.2018.10.029
|View full text |Cite
|
Sign up to set email alerts
|

US Immigration Westernizes the Human Gut Microbiome

Abstract: Summary Many United States immigrant populations develop metabolic diseases post-immigration, but the causes are not well understood. Although the microbiome plays a role in metabolic disease, there have been no studies measuring the effects of U.S. immigration on the gut microbiome. We collected stool, dietary recalls, and anthropometrics from 514 Hmong and Karen individuals living in Thailand and the U.S., including first- and second-generation immigrants and 19 Karen individuals sampled before and after imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
523
7
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 600 publications
(556 citation statements)
references
References 70 publications
24
523
7
2
Order By: Relevance
“…The gut microbiome is influenced by several factors including diet [2], physical activity [3], use of antibiotics [4], and other lifestyle-related conditions. Studies comparing the microbiome of rural and industrialized communities have also shown that dietary and lifestyle changes linked to Westernization have played a pivotal role in the loss of many microbial taxa and in the rise of others [5][6][7][8][9][10][11][12][13][14]. Although it is difficult to establish causality and mechanisms for these links [15,16], recent studies have extended the identifiable members of the human microbiome to now cover > 90% of its overall diversity [11], which is a prerequisite for advancing the understanding of the role of microbes in human physiology and metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…The gut microbiome is influenced by several factors including diet [2], physical activity [3], use of antibiotics [4], and other lifestyle-related conditions. Studies comparing the microbiome of rural and industrialized communities have also shown that dietary and lifestyle changes linked to Westernization have played a pivotal role in the loss of many microbial taxa and in the rise of others [5][6][7][8][9][10][11][12][13][14]. Although it is difficult to establish causality and mechanisms for these links [15,16], recent studies have extended the identifiable members of the human microbiome to now cover > 90% of its overall diversity [11], which is a prerequisite for advancing the understanding of the role of microbes in human physiology and metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have identified host genetics as a crucial determinant of the gut microbiota (Bonder et al, 2016;Kurilshikov, Wijmenga, Fu, & Zhernakova, 2017), which varies not only between species due to differences in the digestive tract characteristics and functions (Ley et al, 2008), but also within species, with genetically similar individuals having greater gut microbial similarities than genetically different individuals (Goodrich et al, 2016(Goodrich et al, , 2014. However, recent studies have indicated that environmental factors play more crucial roles in shaping the gut microbiota than host genetics (Barelli et al, 2015;David et al, 2014;Nelson, Rogers, Carlini, & Brown, 2013;Rothschild et al, 2018;Vangay et al, 2018), with genetically unrelated individuals who live together in the long term having similar gut microbiota and relatives who live apart exhibiting significant differences in their gut microbiota (Rothschild et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The effects of the environment on the gut microbiota are strongly associated with diet (Amato et al, 2016;Barelli et al, 2015;Gomez et al, 2015;Scott, Gratz, Sheridan, Flint, & Duncan, 2013), with the gut microbiome of mammals exhibiting varied responses to altered dietary patterns (Angelakis et al, 2016;David et al, 2014;Muegge et al, 2011). For example, the gut microbiome of US immigrants from non-Western countries is characterized by reduced diversity and functional losses compared with those of preimmigration and newly arrived individuals (Vangay et al, 2018). Furthermore, a study on the effects of the 1975 Japanese diet (a more diverse and healthy dietary pattern than the modern Japanese diet) on the gut microbiota revealed that after 28 days, the proportions of unclassified Lachnospiraceae, Parabacteroides spp., and unclassified Rikenellaceae had significantly decreased and the proportion of Sutterella spp.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, a recent study has shown that migration to the US from Thailand is associated with a loss of bacterial enzymes linked to fibre degradation and a loss of gut microbial diversity (Vangay et al . ). Higher production of SCFAs has also been demonstrated with higher fibre intakes, for example in a study comparing African Americans to native Africans (who have typically higher fibre diets) (Ou et al .…”
Section: Are Diets Low In Prebiotics Detrimental To Gut Health?mentioning
confidence: 97%